2021
DOI: 10.11648/j.wros.20211001.11
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Multipurpose Tree Species Integrated with Moisture Conservation Structures on Degraded Area Closure at Babille District, Ethiopia

Abstract: Tree planting on degraded lands plays a key role in forest rehabilitation processes through afforestation and/or reforestation. Moisture conservation structures have significant impact on seedling survivals at degraded lands. The objectives of this study were to evaluate the effect of moisture conservation structures on seedling survival and growth performance of selected tree species. Field experiment was conducted for four (2016)(2017)(2018)(2019)(2020) in degraded area closure at Babile District East Hararg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This suggests that the condition of the study area matches well with the environmental requirements of these species. The finding was similar to the study, which reported that in the fourth year, a higher survival rate (60.12%) was observed for Moringa oleifera in the Babille district [21]. Another study also stated that Moringa oleifera showed good survival rates, with mean values of 100% at Bako conditions [22].…”
Section: Survival Rate Of Tree Speciessupporting
confidence: 88%
“…This suggests that the condition of the study area matches well with the environmental requirements of these species. The finding was similar to the study, which reported that in the fourth year, a higher survival rate (60.12%) was observed for Moringa oleifera in the Babille district [21]. Another study also stated that Moringa oleifera showed good survival rates, with mean values of 100% at Bako conditions [22].…”
Section: Survival Rate Of Tree Speciessupporting
confidence: 88%
“…In contrast to this, Siyum et al (2019), states that moisture harvesting systems, particularly the eyebrow basin, are considered the most appropriate planting pit in the case of degraded lands in southern Tigray. Cheneke et al (2021), shares a similar opinion when they state that the moisture conservation structures, mainly trenches, are considered the most appropriate planting pit for degraded area closure in Babille district, Ethiopia. For example, Cheneke et al (2021), states that the mean survival of seedlings planted in trenches (65 %) is higher than in normal pits (57 %), and soil bunds (56 %), four years after establishment.…”
Section: In-situ Rain Water Harvestingmentioning
confidence: 88%
“…Cheneke et al (2021), shares a similar opinion when they state that the moisture conservation structures, mainly trenches, are considered the most appropriate planting pit for degraded area closure in Babille district, Ethiopia. For example, Cheneke et al (2021), states that the mean survival of seedlings planted in trenches (65 %) is higher than in normal pits (57 %), and soil bunds (56 %), four years after establishment. Disparate to this, Mamo et al (2016), shows that the mean survival of seedlings planted in half-moons (80 %) is higher than in normal pits (73.33 %) and trenches (60 %) three years after establishment in the case 134 of Hawi Gudina district, west Hararghe Zone, Ethiopia.…”
Section: In-situ Rain Water Harvestingmentioning
confidence: 88%
“…This result was in line with the findings of Eyasu et al [21] who found seedlings planted in moisture harvesting structures survived better compared to the conventional pit. Other authors also reported almost all moisture harvesting structures play a crucial role in conserving and storing moisture [35] and have a significant impact on seedling survival [36] on degraded lands.…”
Section: Contribution Of Moisture Harvesting Structures On Seedling S...mentioning
confidence: 93%
“…Therefore, the water collection ditch helped the seedlings to get more moisture advantage to grow better. So many authors [21,36,41] proved the advantage of moisture harvesting structures on tree seedling growth. Generally, the lower site showed better height and diameter increment of seedlings compared to the upper site.…”
Section: Contribution Of Moisture Harvesting Structures On Seedling G...mentioning
confidence: 99%